Improvement of Student Ecoliteracy through Contextual Teaching and Learning Based on Outdoor Study in Elementary Social Studies Learning - Nurbaeti, Iyus; Supriatna, Nana; Zulfikar, Hari Ahmad (International Conference on Elementary Education, 2020)
Ecoliteracy or Ecological Intelligence is intelligence that is built by understanding, awareness and life skills in harmony with the preservation of nature. This study began with an objective observation in the Binekas Elementary School in Bandung regarding the behavior of students related to environmental awareness. The observation of the behavior of class III students totaling 22 people showed that they were not accustomed to separating organic and inorganic waste, as well as damaging and picking vines in the school. This study aims to increase students' ecoliteracy through contextual teaching learning (CTL) based on outdoor study in elementary social studies learning. The teaching and learning process uses CTL with the material 'Protecting the Environment for the Preservation of Plants and Animals ". The purpose of CTL learning based on outdoor study is to improve environmental problems and increase student ecoliteracy. The method used in this research is Classroom Action Research with a design developed by Kemmis and Mc Taggart for 2 cycles. The results showed that there was an increase in students' ecoliteracy in terms of knowledge, skills and attitudes. In the aspect of knowledge, students show a good understanding of the importance of maintaining hygiene in school. In the aspect of attitude, students show awareness to protect their environment. It was also practiced among other things accustomed to separating organic and inorganic waste, as well as maintaining plants around the school